2021
DOI: 10.1039/d0cc07856e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen doped carbon spheres with wrinkled cages for the selective oxidation of 5-hydroxymethylfurfural to 5-formyl-2-furancarboxylic acid

Abstract: Nitrogen doped carbon spheres with wrinkled cages exhibited high catalytic activity and selectivity in the oxidation of 5-hydroxymethylfurfural to 5-formyl-2-furancarboxylic acid using TBHP as the oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…N dopants with diverse configurations in the carbon skeleton were reported to be responsible for the catalytic activity in electrochemical reactions, selective oxidations, hydrochlorination reactions, dehydrogenation reactions, and so forth. , In those studies, the correlation between activity and the amount of specific type of N dopants were helpful to understand the intrinsic role of specific type of N dopants on catalysis. For instance, Gupta et al reported that the catalytic efficiency of glycerol oxidation was well described by the amount of pyridinic nitrogen (N P ) in a linear correlation .…”
Section: Resultsmentioning
confidence: 99%
“…N dopants with diverse configurations in the carbon skeleton were reported to be responsible for the catalytic activity in electrochemical reactions, selective oxidations, hydrochlorination reactions, dehydrogenation reactions, and so forth. , In those studies, the correlation between activity and the amount of specific type of N dopants were helpful to understand the intrinsic role of specific type of N dopants on catalysis. For instance, Gupta et al reported that the catalytic efficiency of glycerol oxidation was well described by the amount of pyridinic nitrogen (N P ) in a linear correlation .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the adsorption experiments also indicate that all the Au/CeO 2 samples show the higher HMF adsorption ability than pure CeO 2 samples (Figure S15 and Table S3). According to the active oxygen species capture experiments, the catalytic performance of the control group with p ‐benzoquinone is obviously lower than that of the control with tert ‐butanol and the standard oxygen reaction over Au/rod‐CeO 2 catalyst (Figure S17a, 46.74 vs. 9.40 %) [47,48] . These results indicate that superoxide radical (O 2 .− ) is the main reactive oxygen species, which is formed by interaction between oxygen adsorption and electrons (Figure S17b) [2] .…”
Section: Resultsmentioning
confidence: 99%
“…According to the active oxygen species capture experiments, the catalytic performance of the control group with p-benzoquinone is obviously lower than that of the control with tert-butanol and the standard oxygen reaction over Au/rod-CeO 2 catalyst (Figure S17a, 46.74 vs. 9.40 %). [47,48] These results indicate that superoxide radical (O 2 *À ) is the main reactive oxygen species, which is formed by interaction between oxygen adsorption and electrons (Figure S17b). [2] Therefore, the electron density of occupied 4f orbital is related to the concentration of V O , which depended on exposed crystal faces of CeO 2 -based catalysts.…”
Section: Theoretical Calculation Of Electron Densitymentioning
confidence: 92%
“…Presently, catalysts capable of the selective synthesis of FFCA remain limited, regardless of whether they are chemical or biological. Thermocatalytic conversion of HMF over metal-based and metal-free catalysts was described for producing FFCA at more than 100 °C. Notably, Wu and co-workers reported an effective and selective method for the HMF oxidation using H 2 O 2 under relatively mild conditions (e.g., 75 °C) in water, based on activated carbon-supported ruthenium; FFCA was obtained in 92% yield with a HMF/catalyst ratio of 50 in 1 h . Visible light-fueled conversion of HMF to FFCA over graphitic carbon nitride (g-C 3 N 4 )/NaNbO 3 was reported in water, with the HMF conversion of approximately 36% and the FFCA selectivity of 87% .…”
Section: Catalytic Oxidationmentioning
confidence: 99%